The Effect of Denture Base Surface Treatments on Microlekage of Soft Lining Materials - Munther N. Kazanji; Nadia T. Jaffer (University of Mosul, College of Dentistry, 2009)
Aims: To evaluate the effect of two acrylic resin denture base surface trearments on microleakageof 4 soft denture lining materials (Tru-soft, Bony plus, UfiGel-P and Molloplast-B after 2 periods ofstorage and thermalcycling. Materials and methods: One hundred eighty specimens for microleakagewere prepared in a disc shape 30 mm diameter and 4 mm thickness (2 mm for acrylic resin part and 2mm for soft lining material part). Soft lining materials were bonded to three different groups ofacrylic resin surface pretreatments (untreated, sandblasted and monomer treated denture base). Thesespecimens underwent two aging procedures: Storage with two periods (one week and one month), and500 cycles of thermalcycling inside 2% methylene blue dye. Results: Statistical analysis showed thattreating the acrylic resin denture base by sandblasting increased microleakage of silicone-based linings(UfiGel-P and Molloplast-B)and decreased microleakage of acrylic-based linings (Tru-soft and Bonyplus) in comparison to untreated denture base, while treating the denture base with MMA monomerpositively decreased microleakage for all tested soft lining materials in relation to untreated andsandblasted denture base at one week storage, one month storage and at thermalcycling. Conclusions:For all types of denture base surface treatments, microleakage was inevitable, however, wetting theacrylic resin denture base with MMA monomer was more effective in reducing microkeakage thansandblasted and untreated denture bases.